Perancangan Dan Pembuatan Sistem Informasi Penilaian Pada SMA Santo Thomas 4 Binjai Berbasis Web - Edy Budi Harjono Sibarani (PT. ALHAFI BERKAH INDONESIA, 2025)
The influence of information and communication technology on the world of education is growing rapidly, shifting learning patterns from face-to-face to media-based learning. SMA Santo Thomas 4 Binjai, focuses on innovation in the field of education. However, the current learning system is still manual, relying on limited teacher-student face-to-face interactions and discussions. This condition causes a lack of target achievement in the learning process. This research aims to design an e-learning information system using the CodeIgniter framework. The choice of CodeIgniter is expected to facilitate e-learning, increase efficiency and accuracy of learning management. System development using PHP and MySQL, with design based on UML principles. The results of the research produced an e-learning information system which aims to increase understanding in the teaching and learning process at SMA Santo Thomas 4 Binjai. This system is expected to support more dynamic interaction between teachers and students, as well as speed up the learning process according to the SDLC method. SMA Santo Thomas 4 Binjai has the potential to improve the quality of learning, facilitate better interaction, and speed up the learning process according to strategic achievements.